Tuning Microbial Activity via Programmatic Alteration of Cell/Substrate Interfaces. Issue 46 (24th May 2021) - Gulyuk, Alexey V.; LaJeunesse, Dennis R.; Collazo, Ramon; Ivanisevic, Albena
Abstract: A wide portfolio of advanced programmable materials and structures has been developed for biological applications in the last two decades. Particularly, due to their unique properties, semiconducting materials have been utilized in areas of biocomputing, implantable electronics, and healthcare. As a new concept of such programmable material design, biointerfaces based on inorganic semiconducting materials as substrates introduce unconventional paths for bioinformatics and biosensing. In particular, understanding how the properties of a substrate can alter microbial biofilm behavior enables researchers to better characterize and thus create programmable biointerfaces with necessary characteristics on demand. Herein, the current status of advanced microorganism–inorganic biointerfaces is summarized along with types of responses that can be observed in such hybrid systems. This work identifies promising inorganic material types along with target microorganisms that will be critical for future research on programmable biointerfacial structures. Abstract : Concepts of inorganic substrate/microorganism biointerfaces that can serve as "smart" materials with desired reactions to external conditions are discussed. Understanding how such sophisticated structures may be formulated and various types of their responses is essential for the discovery of novel approaches in the areas of biosensing, bioelectronics, and biocompatible materials.